Nasopalatine duct cyst - Matijević Stevo; Gazivoda Dragan; Marjanović Marjan; Udovičić Božidar (Vojnosanitetski Pregled, 2007)
Background. Nasopalatine duct cyst is a developmental, nonodontogenic cyst of jaw. Case report. We presented a 46-year-old male with nasopalatine duct cyst. The clinical examination revealed fluctuant swellings of the anterior palate, without pain, 4−5 cm in diametar. Both radiographs showed the presence of an ovoid radiolucency located in the midline of the maxilla between the roots of central maxillary incisor teeth with peripheral sclerosis, 25 × 35 cm in diametar. Surgical treatment was performed under local anaesthesia (ArticainchloridumTM 4% − 3M ESPE) using a palatine approach. Postoperatively, no paresthesia of the anterior palate in inervation area of nasopalatine nerve was registrated. Pathohistologic findings proved both clinical and radiological diagnosis. Conclusion. Nasopalatine duct cyst is a rare lesion which slowly develops. The diagnosis is mainly based on radiography, tooth vitality testing and histologic findings. After a correctly applied clinical diagnosis procedure and surgicel treatment, recurrence is rare.